Reconstructing the expression of placement events in Danish as a second language - Cadierno, Teresa; Ibarretxe-Antuñano, Iraide; Hijazo-Gascón, Alberto (Frontiers in Psychology, 2023)
Cross-linguistic research on event typology has revealed considerable variation in the linguistic conceptualization of placement events. Previous studies on second language acquisition have primarily dealt with the semantic re-categorization of placement verbs in a second language, but placement constructions have received less attention. The present study fills this gap by examining the constructions used by Spanish learners of L2 Danish (B1 and B2 levels) and by monolingual speakers of both languages. Data were elicited by means of the PUT task consisting of oral video descriptions and then classified into six main placement construction categories based on their frequency and structure. Results from the learner group suggest learning difficulties when reconstructing the expression of placement events in L2 Danish. In contrast to L1 Danish data, learners (i) kept using their L1 Spanish basic placement construction more often, (ii) avoided semantically more complex constructions, (iii) employed fewer spatial particles, (iv) showed difficulties in selecting the L2 appropriate spatial particles for specific placement scenes, and (v) used non-caused motion constructions. These findings suggest the creation of a linguistic conceptualization pattern on the part of the learners that is different from the respective L1 and L2 monolingual patterns, thus providing further empirical support for proposals arguing that bilinguals’ multicompetence is not equivalent to those of two monolinguals.